2019
DOI: 10.4067/s0717-95022019000401463
|View full text |Cite
|
Sign up to set email alerts
|

Mimosine Increases the Expressions of Tyrosine Phosphorylated Protein in Mouse Seminal Vesicles

Abstract: Acute effect of purified mimosine (MiMo) extracted from Leucaena leucocephala on testicular histopathology has been documented with seminal vesicle (SV) atrophy. Since protein phosphorylation and seminal secretions play important roles in sperm physiology, this study aimed to study the alteration of substances including tyrosine phosphorylated (TyrPho) proteins in seminal vesicle treated with MiMo. Male mice were divided into a control and experimental groups treated with purified MiMo at 3 doses of 15, 30, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Many studies have reported that expressions of testicular TyrPho proteins are altered in infertile conditions associated with decrease in testosterone level (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, 2016; Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, 2016; Burawat et al., 2018; Chaichun et al., 2019; Iamsaard et al., 2014, 2018; Sampannang et al., 2019; Sukhorum & Iamsaard, 2017). We assumed that the overexpression of testicular TyrPho proteins may associate with decreased testosterone level or involved in early apoptotic process in seminiferous epithelium of ethanol‐treated animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that expressions of testicular TyrPho proteins are altered in infertile conditions associated with decrease in testosterone level (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, 2016; Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, 2016; Burawat et al., 2018; Chaichun et al., 2019; Iamsaard et al., 2014, 2018; Sampannang et al., 2019; Sukhorum & Iamsaard, 2017). We assumed that the overexpression of testicular TyrPho proteins may associate with decreased testosterone level or involved in early apoptotic process in seminiferous epithelium of ethanol‐treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many tyrosine-phosphorylated (TyrPho) proteins have been localised and identified in testis, epididymis and seminal vesicle of rats (Chaichun, Arun, Burawat, Kanla, & Iamsaard, 2017;Sawatpanich et al, 2018;Tongpan, Sukhorum, Arun, Sawatphanich, & Iamsaard, 2019). Indeed, the alteration of TyrPho proteins is associated with male infertile conditions such as animals induced with anti-cancer drugs (Burawat, Uabandit, Arun, Nualkaew, & Iamsaard, 2018;Chaichun et al, 2019;Iamsaard et al, 2014Iamsaard et al, , 2018Sukhorum & Iamsaard, 2017;Tongpan et al, 2019), type 1 and 2 diabetes (Sampannang, Arun, Burawat, Sukhorum, & Iamsaard, 2019;Yannasithinon & Iamsaard, 2019), and acute and chronic stresses (Arun, Burawat, Sukhorum, Sampannang, Maneenin, et al, 2016;Arun, Burawat, Sukhorum, Sampannang, Uabundit, et al, 2016). However, the changes in testicular TyrPho proteins and other markers in sexually mature rats administered with ethanol have never been reported.…”
mentioning
confidence: 99%
“…Tyrosine phosphorylation (TyrPho) is an essential process involved in many physiological mechanisms such as cellular signaling pathways. Particularly, the alterations of TyrPho proteins in reproductive system have been shown to be sensitive to cancer drug treatments (Iamsaard et al, 2014;Iamsaard et al, 2017;Iamsaard et al, 2018;Sawatpanich et al;Chaichun et al, 2019;Tongpan et al), diabetic mellitus (Yannasithinon & Iamsaard, 2009;Sampannang et al, 2018Sampannang et al, , 2019, and stress conditions (Arun et al, 2016a(Arun et al, ,b, 2018. Currently, it has been reported that the decreased expression of a TyrPho protein in kidney induced by valproic acid, an antiepileptic drug, is associated with the increased malondialdehyde levels and renal vasodilation (Maneenin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The biological effect of those anti-nutritive molecules directly affects the digestibility of protein and carbohydrates (Román-Cortés et al, 2014;Tran et al, 2016). The non-protein amino acid called mimosine, acid (S)-α-Amino-β-[1-(3-hydroxy-4oxopyridin), inhibits some intracellular processes (Tran et al, 2016;Chaichun et al, 2019) and can be used as an immunosuppressive, antiarrhythmic and hypocholesterolemic agent (Syamsudin et al, 2010). The use of leucaena seeds as an ingredient in livestock feed has been widely evaluated (Barác et al, 2015), but their use in human food has not been formally studied.…”
mentioning
confidence: 99%